Convective heat transfer characteristics in the turbulent region of molten salt in concentric tube. (5th April 2016) - Chen, Y.S.; Wang, Y.; Zhang, J.H.; Yuan, X.F.; Tian, J.; Tang, Z.F.; Zhu, H.H.; Fu, Y.; Wang, N.X.
Abstract: In order to better understand the heat transfer behavior and characteristics of molten salt in heat exchanger, the convective heat transfer characteristics of molten salt in salt-to-oil concentric tube are studied. Overall heat transfer coefficients of the heat exchanger are calculated using Wilson plots. Heat transfer coefficients of tube side molten salt with the range of Reynolds number from 10, 000 to 50, 000 and the Prandtl number from 11 to 27 are evaluated invoking the calculated overall heat transfer coefficients. The effects of velocity and temperature on the convective heat transfer in the turbulent region of molten salt are studied by comparing with the traditional correlations. The results show that the heat transfer characteristics of molten salt are in line with the empirical heat transfer correlation; however, Dittus–Boelter, Gnielinski, Sieder–Tate and Hausen correlations all give a larger deviation for the experimental data. Finally, based on the experimental data and Sieder–Tate correlation, a modified heat transfer correlation is proposed and good agreement is observed between the experimental data and the modified correlation. The results will also provide an important reference for the design of the heat exchangers in the Thorium-based Molten Salt Reactor.